The Effect of Cartoon Character Role Play for Students’ Speaking Fluency and Confidence - Siti Fatimah; Mukrim Mukrim; Sukmawati Sadilia (Universitas Pahlawan Tuanku Tambusai, 2026)
Speaking is a fundamental component of English language learning that enables students to communicate ideas effectively in academic and social contexts. Among the key aspects of speaking, fluency facilitates smooth and coherent communication, while confidence supports students in expressing their ideas without excessive hesitation or anxiety. However, many lower secondary school students continue to experience difficulties in these areas. This study aimed to examine the effect of Cartoon Character Role Play on students’ speaking fluency and confidence. A quantitative approach employing a pre-experimental one-group pre-test and post-test design was used. The participants were 25 ninth-grade students of MTs Alkhairaat Mamboro. Data were collected through speaking performance tests and analyzed using SPSS. The findings revealed that the mean score increased from 44.5 in the pre-test to 56 in the post-test. Furthermore, the paired sample t-test yielded a significance value of 0.000 (p 0.05), indicating that Cartoon Character Role Play significantly improved students’ speaking fluency and confidence.